Neural Tube Defects Prevention with Folic Acid Supplementation and Fortification: A Comprehensive Systematic Review - Purnasari, Henni; Juliana, Mutia (The Indonesian Journal of General Medicine, 2024)
Background: Neural tube defects (NTDs), affecting 1–2 per 1000 live births globally, leading to significant health and economic burdens. Folate supplementation and food fortification are crucial for prevention. The aim of this systematic review is to comprehensively evaluate the role of folate fortification and supplementation in reducing the incidence of NTDs. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Folic acid supplementation and fortification are effective in lowering global NTD rates, despite disparities in implementation and outcomes, especially in low-resource areas.